Direct applicability and direct invocability of the WTO Agreement in the case of the WTO Trade Facilitation Agreement (TFA)in Indonesia - Ersya, Ozy-Diva (2019)
Having been concluded at the 2013 Bali Ministerial Conference, the WTO TFA entered into force on 22 February 2017. Indonesia became the 125th WTO Member to deposit the ratification instrument to the WTO on 5 December 2017 and prior to that had already given its domestic approval for the WTO TFA through Law No. 17/2017 dated 22 November 2017. However, there is legal ambiguity attached to the direct applicability of a treaty in Indonesian domestic law. This includes the WTO Agreement and particularly the WTO TFA. Regardless of the categorisation system provided under SDT provisions for the implementation, Indonesia’s ratification to the WTO TFA has let the WTO believed that, on the one hand, Indonesia is committed to implement the WTO TFA provisions in domestic law, but on the other hand, to keep the ambiguity present in domestic law. Unlike any other WTO Agreements in Annex 1A, the WTO TFA is based on cooperative approach in the implementation of its provisions instead of reciprocity principle. The approach is momentous to the invocation of its provisioned rights for private actors which is argued to consist of two rights: substantive economic rights and procedural rights. They may need it both as a sword to cut down any unnecessary trade costs and a shield to protect them from trade difficulties. The case of Indonesia shows a WTO member with excessive trade costs in cross border and protectionist laws. The protection of private actor rights to prevent them from inappropriate treatment has therefore taken on some urgency. The rationale is to reduce unnecessary trade costs and unveiling trade protectionism which disadvantages them. A proposal for improvement in the implementation of trade facilitation reform in Indonesia for the benefit of government and private actors is also submitted. Nevertheless, allowing or precluding such invocation of those rights is a matter of the applicable law of a state– in this case, Indonesia.